Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1063/1.4802952
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial perpendicular magnetic anisotropy and damping parameter in ultra thin Co2FeAl films

Abstract: B2-ordered Co2FeAl films were synthesized using an ion beam deposition tool. A high degree of chemical ordering ∼81.2% with a low damping parameter (α) less than 0.004 was obtained in a 50 nm thick film via rapid thermal annealing at 600 °C. The perpendicular magnetic anisotropy (PMA) was optimized in ultra thin Co2FeAl films annealed at 350 °C without an external magnetic field. The reduced thickness and annealing temperature to achieve PMA introduced extrinsic factors thus increasing α significantly. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 26 publications
1
35
1
Order By: Relevance
“…[16][17][18] Very recently, the interface-induced PMA was discovered in a Co-based FHA (Co 2 FeAl) in contact with a MgO oxide layer. 19,20 The proposed explanation for the PMA is similar to that of CoFeB or Fe/MgO systems for which interfacial anisotropy induced by hybridization of Fe-, Co-3d and O-2p orbitals causes the a Electronic email: dau@pdi-berlin. PMA.…”
Section: Introductionmentioning
confidence: 91%
“…[16][17][18] Very recently, the interface-induced PMA was discovered in a Co-based FHA (Co 2 FeAl) in contact with a MgO oxide layer. 19,20 The proposed explanation for the PMA is similar to that of CoFeB or Fe/MgO systems for which interfacial anisotropy induced by hybridization of Fe-, Co-3d and O-2p orbitals causes the a Electronic email: dau@pdi-berlin. PMA.…”
Section: Introductionmentioning
confidence: 91%
“…Ferromagnetic resonance (FMR) spectra were acquired using a broadband coplanar waveguide field-swept setup with frequencies up to 50 GHz. The frequency dependence on the linewidth was used to estimate an effective damping parameter 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ferromagnetic resonance measurements were performed on CoFeCrB films, showing a much lower damping parameter compared to the values reported in the previous literature 9 . 12 ) were co-sputtered with different power ratios. By varying the powers applied to the two targets, the Cr content can be systematically changed from 10% to 30 %, along with a reducing Fe content.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that K S was the main contribution leading to the PMA at a Co 2 FeAl/MgO interface [72].…”
Section: Perpendicular Magnetic Anisotropy (Pma)mentioning
confidence: 99%
“…It was considered as a promising electrode for perpendicular MTJs because of the PMA at the Co 2 FeAl/MgO interfaces [72].…”
Section: Materials Candidates For Stno 261 Heusler Alloy Co 2 Fealmentioning
confidence: 99%